Evaluation of HLA-G immune checkpoint molecule in melanocytic lesions - Raylane P Gomes; Gabriela Tayrine Caetano; Lucas Henrique F Sampaio; Camila R Silva; Maurício B Costa; Maria Auxiliadora Cysneiro; Isabela Jubé Wastowski (Sociedade Brasileira de Patologia Clínica, 2020)
ABSTRACT The human leukocyte antigen-G (HLA-G) is a non-classical molecule of the major histocompatibility complex. HLA-G has been associated with the process of tumorigenesis and tumor escape. In this study, we aim to evaluate the HLA-G expression in melanocytic lesions and in melanoma for determining when melanocytic lesions start its expression. Twenty-two skin biopsies samples were submitted to immunohistochemistry; HLA-G expression was detected in 63.6% of the samples. This expression in melanocytic cells was significantly higher in melanoma than in benign melanocytic lesions (p < 0.002). Our results suggest that HLA-G expression starts late in the process of tumorigenesis.